Characterization of Trichuris trichiura from humans and T. suis from pigs in China using internal transcribed spacers of nuclear ribosomal DNA. Issue 1 (March 2014) - Liu, G.H.; Zhou, W.; Nisbet, A.J.; Xu, M.J.; Zhou, D.H.; Zhao, G.H.; Wang, S.K.; Song, H.Q.; Lin, R.Q.; Zhu, X.Q.
Abstract Trichuris trichiura and Trichuris suis parasitize (at the adult stage) the caeca of humans and pigs, respectively, causing trichuriasis. Despite these parasites being of human and animal health significance, causing considerable socio-economic losses globally, little is known of the molecular characteristics of T. trichiura and T. suis from China. In the present study, the entire first and second internal transcribed spacer (ITS-1 and ITS-2) regions of nuclear ribosomal DNA (rDNA) of T. trichiura and T. suis from China were amplified by polymerase chain reaction (PCR), the representative amplicons were cloned and sequenced, and sequence variation in the ITS rDNA was examined. The ITS rDNA sequences for the T. trichiura and T. suis samples were 1222–1267 bp and 1339–1353 bp in length, respectively. Sequence analysis revealed that the ITS-1, 5.8S and ITS-2 rDNAs of both whipworms were 600–627 bp and 655–661 bp, 154 bp, and 468–486 bp and 530–538 bp in size, respectively. Sequence variation in ITS rDNA within and among T. trichiura and T. suis was examined. Excluding nucleotide variations in the simple sequence repeats, the intra-species sequence variation in the ITS-1 was 0.2–1.7% within T. trichiura, and 0–1.5% within T. suis. For ITS-2 rDNA, the intra-species sequence variation was 0–1.3% within T. trichiura and 0.2–1.7% within T. suis. The inter-species sequence differences between the two whipworms were 60.7–65.3% for ITS-1 and 59.3–61.5% for ITS-2. These results demonstrated that the ITS rDNA sequences provide additional genetic markers for the characterization and differentiation of the two whipworms. These data should be useful for studying the epidemiology and population genetics of T. trichiura and T. suis, as well as for the diagnosis of trichuriasis in humans and pigs.